Work-life Balance among Working Women: Systematic Literature Review on Its Influencing Factors - Aprilia, Reza Tamafaya; Hayati, Elli Nur; Situmorang, Nina Zulida (Al Huwiyah: Journal of Woman and Children Studies, 2025)
Women workers often face challenges in managing the demands of work and personal life, which impacts their well-being and lives. This systematic literature review aims to identify factors that influence work-life balance in female workers. The guidelines used in this study are Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Populations, Exposure, Outcomes, and Study Design (PEOS) framework to select relevant articles. The factors analysed included organisational, psychological, and social aspects. In the organisational aspect, factors such as job satisfaction, organisational support, organisational culture, work environment, and work overload were found to affect the work-life balance of female workers. Psychological well-being, emotional intelligence, and coping mechanisms were found in the psychological aspect. Family, friends, and coworkers' support was found on the social aspect. These findings contribute to the development of policies that can support women workers in carrying out their dual roles and further research. Keywords: gender, female workers, work-life balance.